2008
DOI: 10.1667/rr1121.1
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Changes in the Skin of Rats Induced by Prolonged 35 GHz Millimeter-Wave Exposure

Abstract: To better understand the cellular and molecular responses to overexposure to millimeter waves, alterations in the gene expression profile and histology of skin after exposure to 35 GHz radiofrequency radiation were investigated. Rats were subjected to sham exposure, to 42 degrees C environmental heat, or to 35 GHz millimeter waves at 75 mW/cm(2). Skin samples were collected at 6 and 24 h after exposure for Affymetrix GeneChip analysis. The skin was harvested from a separate group of rats at 3-6 h or 24-48 h af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
29
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 38 publications
(48 reference statements)
5
29
1
Order By: Relevance
“…Therefore, the energy of a millimeter wave can be absorbed by the organism through resonance. In turn, the energy can interfere with signal transduction and affect metabolism (8)(9)(10). It has been shown that a millimeter wave can evoke multiple biological effects (11,12) and is useful in the treatment of various types of diseases including cancers, such as hepatic cellular cancer patient (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the energy of a millimeter wave can be absorbed by the organism through resonance. In turn, the energy can interfere with signal transduction and affect metabolism (8)(9)(10). It has been shown that a millimeter wave can evoke multiple biological effects (11,12) and is useful in the treatment of various types of diseases including cancers, such as hepatic cellular cancer patient (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…A few well-characterized stressors include hyperthermia, hypoxia, ionizing and non-ionizing radiation, ATP depletion, oxidative stress, and pathogenic stimuli (Schreck et al 1992;Feder and Hofmann 1999;Kabakov et al 2002;Kultz 2005;Diller 2006;Miller 2006;Millenbaugh et al 2008). At the cellular level, stressors can inflict strain on intracellular biomolecules (e.g., lipids, proteins, and DNA, and if such strain is appreciable, these biomolecules can undergo structural modifications that can preclude them from functioning properly.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the energy of MW can be absorbed by the organism through resonance. In turn, the energy may interfere with signal transduction and affect metabolism (10)(11)(12)(13). MW has been shown to evoke multiple biological effects and is beneficial in the treatment of OA.…”
Section: Introductionmentioning
confidence: 99%